Integrating multiple clinical information systems using the Java Message Service framework. - Tellis WM; Andriole KP (Journal of Digital Imaging, 2004)
This article describes an application for capturing, delivering, and tracking urgent radiology exam results. Urgent exam findings are entered using a Web form embedded within the Picture archiving and communication system (PACS) display station. The findings are then accessible via soft copy using the PACS display stations, hospital information system (HIS) terminals, or wireless-enabled personal digital assistants (PDAs) or via hard copy printouts that are generated automatically or on demand. Additionally, quality control is performed on those findings entered by radiology residents and fellows, the results of which are used for both performance tracking and educational activities. The application was developed using Sun Microsystems' Java programming language. The Java Message Service (JMS) was used to manage the delivery of findings. JMS provides a robust, flexible framework for exchanging messages between disparate applications. The application is now used for all urgent exams; completely replacing the original paper-based system. The use of JMS provides the necessary level of reliability needed by this application.